Effect of Occupants' Behaviour of Daylight Controls on Residential Visual Environment. Issue 1 (February 2013) - Shin, Hwa Young; Kim, Gon; Kim, Jeong Tai
This paper aims to assess how occupants perceived their visual environments of diverse luminous ambiences created by daylight in apartment buildings. Daylighting can have a large influence on environmental condition to improve ambience, visual comfort, well-being and health of occupants. Thus, it is essential to understand what visual adaptive actions for the satisfaction of occupants and how they respond to given visual environments. A purpose-built living room with balcony extension was situated at Kyung Hee University in Korea (latitude 37.17N, longitude 127.01E) to monitor data throughout a 1-month period in winter. Thirty-two subjects participated and each subject spent a day in the test room. All subjects were given the opportunity to have artificial lighting and blinds control over the lighting ambience appropriate for their activity. Physical measurements such as illuminance levels of vertical and floor-planes, window luminance were monitored simultaneously which were cross-linked to the subjective assessment of blinds control. Experimental results revealed the factors affecting the occupant use of shading systems; visual comfort, seating orientation and blinds types could have an effect. The results of this study should provide useful information on daylighting as a function of photometrical and behavioural factors for future application in building design.